A >3000 suns high concentrator photovoltaic design based on multiple Fresnel lens primaries focusing to one central solar cell. (15th July 2018) - Shanks, Katie; Ferrer-Rodriguez, Juan P.; Fernández, Eduardo F.; Almonacid, Florencia; Pérez-Higueras, Pedro; Senthilarasu, S.; Mallick, Tapas
Highlights: The design is capable of higher concentration ratios than other CPV designs currently in literature. Even with low quality optics, the simulated design still achieves >3000x. A high refractive index multi-entry central receiver optic allows for high concentration and CAP. The use of state of the art optics increases the optical concentration ratio to 4373x. Partial assembly of the system confirms easy manufacturing and working design concept. Abstract: A high concentrator photovoltaic design is proposed of 5800x geometrical concentration ratio based on multiple primary Fresnel lenses focusing to one central solar cell. The final stage optic is of a novel design, made of a high refractive index (n = ∼1.76), to accept light from four different directions but very easily manufactured. The high geometrical concentration of 5800x was chosen in anticipation of the losses accompanied due to alignment difficulties. Two scenarios are however simulated, one with state of the art optics (achromatic Fresnel lenses and 98% reflective mirrors) and one of standard, relatively cheap optics. An optical efficiency of ∼75% is achieved in simulations if high quality optics are utilised, which gives an optical concentration ratio of just over 4300x. Simulating standard optical constraints with less accurate optics results in an optical efficiency of ∼55% which translates to an optical concentration ratio of ∼3000x. In this way the quality of the optics can be chosen depending on the trade of between cost and efficiency with room for future advanced optics to be incorporated at a later date. The optical efficiency of each component is simulated as well as experimentally measured to ensure the accuracy of the simulations. A theoretical acceptance angle of 0.4° was achieved in ray trace simulations for this design which is considered good for such a high concentration level. The need for achromatic Fresnel lenses is apparent from this study to reach optimum performance and concentration but even 55% optical efficiency results in a >3000x concentration not yet experimentally tested. The solar cells irradiance distribution of the design is also presented along with performance and rough cost comparisons to other systems in the literature. The cost of the optics compared to more complex shaped optics is also given.